Kontribusi Kepemimpinan Transformasional, Religiusitas, Budaya Sekolah dan Kecerdasan Emosional Terhadap Kinerja Guru SMA Muhammadiyah di Bali - N.A. Yani; I.P.W. Ariawan; I.G.K.A Sunu (Jurnal Administrasi Pendidikan Indonesia, 2022)
This research aims to determine: 1) the contribution of transformational leadership towards teachers’ performance, 2) the contribution of religiosity towards teachers’ performance, 3) the contribution of school culture towards teachers’ performance, 4) the contribution of emotional intelligence towards teachers’ performance, 5) the contribution of transformational leadership, religiousity, school culture, and emotional intelligence simultaneously towards the teachers’performance of Muhammadiyah high schools in Bali. The population of this study was 46 teachers. This study is classified as ex-post-facto with descriptive statistics analysis, simple correlation, partial correlation, multiple correlation, and multiple regression data analysis design. Data collection for this study was conducted by using the Five-point Likert scale questionnaire model. The results of the study show that: 1) There is a positive and significant correlation between transformational leadership and teachers’ performance with 0,464 (ryx1) product moment coefficient correlation, 0,324 (ry.x1-x2,3,4) partial correlation coefficient, and 12,94% contribution of transformational leadership towards teachers’ performance, 2) There is a positive and significant correlation between religiosity and teachers’ performance with 0,546 (ryx2) product moment coefficient correlation, 0,354 (ry.x2-x,3,4) partial correlation coefficient, and 18,07% contribution of religiosity towards teachers’ performance, 3) There is a positive and significant correlation between school culture and teachers’ performance with 0,513 (ryx3) product moment coefficient correlation, 0,384 (ry.x3-x1,2,4) partial correlation coefficient, and 16,01%, contribution of school culture towards teachers’ performance, 4) There is a positive and significant correlation between emotional intelligence and teachers’ performance with 0,422 (ryx4) product moment coefficient correlation, 0,316 (ry.x4-x1,2,3) partial correlation coefficient, and 10,88%, contribution of emotional intelligence towards teachers’ performance, 5) There is a positive and significant correlation of transformational leadership, religiosity, school culture, emotional intelligence, and teachers’ performance simultaneously by 57,9%..